EARNED SURPLUS. (The Accounting Review, 1930)
Abstract This article presents information on the report of the committee of the American Institute's on the definition on earned surplus. The definition, as finally revised, follows: "Earned surplus is the balance of the net profits, net income, and gains of a corporation after deducting losses and after deducting distributions to stockholders and transfers to capital-stock accounts." Further on in the committee's report net profits, net income, and gains are described as including "profits from the disposition of any corporate asset and arise from transactions resulting in the acquisition of cash or of property which at the time of its receipt may ordinarily be classified as or converted into, a current asset or from transactions in which the consideration received includes the complete or partial discharge of a liability." The hope is thus indirectly expressed that any newly-created revaluation surplus will be treated as indicated in last year's report. Disclosures and qualifications and their repetition on successive balance sheets are subjects concerning which much remains unsaid. They are likely to be the subjects of rules of conduct which the future holds in store for the profession. In the meantime they must be discussed fully and frankly if definitions and uniform practices are to be adopted by the profession and their wording must be significant and must, furthermore, become a definite addition to the parlance of the financial world.